Late-life physical activity, midlife-to-late-life activity patterns, APOE ε4 genotype, and cognitive impairment among Chinese older adults: a population-based observational study - Xunying Zhao; Xueyao Wu; Tianpei Ma; Jinyu Xiao; Xin Chen; Mingshuang Tang; Li Zhang; Tao Zhang; Mengyu Fan; Jiaqiang Liao; Ben Zhang; Xia Jiang; et al. (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Although physical activity (PA) has been linked to cognitive health, the nuanced relationships between different dimensions of PA and cognitive impairment remain inconclusive. This study investigated associations between late-life PA levels, midlife-to-late-life activity patterns, and cognitive impairment in Chinese older adults, considering potential moderation by apolipoprotein E (APOE) ε4 genotype. Methods We analyzed baseline data from 6,899 participants (median age 68 years, 55.78% female) in the West China Health and Aging Cohort study, with 6,575 participants having APOE genotyping data. Late-life PA and midlife-to-late-life activity patterns were assessed using the Global Physical Activity Questionnaire and a standardized question, respectively. Cognitive function was evaluated using the Chinese version of Mini-Mental State Examination. Logistic regression models were used to examine associations. Results Compared to low PA level, moderate (odds ratio [OR] = 0.74, 95% confidence interval [CI] = 0.55 ~ 0.99) and high PA levels (OR = 0.60, 95%CI = 0.48 ~ 0.75) were associated with lower risk of cognitive impairment. Engaging in work-, transport-, recreation-related, and moderate-intensity PA were each significantly associated with lower cognitive impairment risk. Maintaining activity levels from midlife to late life was associated with lower cognitive impairment risk compared to decreasing levels (OR = 0.75, 95%CI = 0.60 ~ 0.94). These associations were more pronounced in APOE ε4 non-carriers, with an interaction observed between APOE ε4 genotype and recreation-related PA (P-value = 0.04). Conclusions Our findings underscore the multifaceted benefits of PA in mitigating cognitive impairment risk among older Chinese adults. Public health strategies should focus on promoting overall late-life PA levels, especially moderate-intensity PA, and maintaining activity levels comparable to midlife, with potential for personalized interventions based on genetic risk profiles.